PENGARUH BUSINESS PLAN DAN DIGITAL MARKETING TERHADAP KETAHANAN UMKM PASCA PANDEMI DI JAKARTA TIMUR - Fitrianingsih, Yuli; Sebayang, Karuniana Dianta Arfiando; Mukhtar, Saparuddin (Transpublika Publisher, 2022)
The objective of this study is to investigate the impact that having a business plan and engaging in digital marketing have had on the resiliency of micro, small, and medium-sized enterprises (MSMEs) in East Jakarta following the pandemic. The population that is the focus of this study is comprised of East Jakarta's 240,512 small and medium-sized businesses. Purposive sampling was used to collect data from these 140 participants to create the sample for this investigation. Processing of data utilizing the SEM (Structural Equation Model) approach with the Smart PLS (Partial Least Squares) tool version 4, which includes the Estimation Test, Evaluation Test, and Mediation Test of the SEM-PLS Model. In light of the results of the hypothesis test, one can reach the following conclusion: the Business Plan variable representing MSME resilience has an influence that is both positive and significant. The influence of digital marketing on the resilience of micro, small, and medium-sized enterprises is positive but insignificant. Meanwhile, the impact of the business strategy on the resiliency of MSMEs is positive but not statistically significant when the intervening variable is digital marketing.